$\color{red}{\left\{ \begin{array}{l} 32x^{5}-5\sqrt{x-2}=y(y-4)\sqrt{y-2}-2x\\ (\sqrt{y-2}-1)\sqrt{2x+1}=8x^{3}-13(y-2)+82x-29 \end{array} \right
.}
\left\{
32x5−5√x−2=y(y−4)√y−2−2x(√y−2−1)√2x+1=8x3−13(y−2)+82x−29 \right.$
Hệ phương trình
\displaystyle{\color{red}{\left\{ \begin{array}{l} 32x^{5}-5\sqrt{x-2}=y(y-4)\sqrt{y-2}-2x\\ (\sqrt{y-2}-1)\sqrt{2x+1}=8x^{3}-13(y-2)+82x-29 \end{array} \right}}{32x5−5√x−2=y(y−4)√y−2−2x(√y−2−1)√2x+1=8x3−13(y−2)+82x−29
Hệ phương trình
$\color{red}{\left\{ \begin{array}{l} 32x^{5}-5\sqrt{x-2}=y(y-4)\sqrt{y-2}-2x\\ (\sqrt{y-2}-1)\sqrt{2x+1}=8x^{3}-13(y-2)+82x-29 \end{array} \right
.}
\left\{
32x5−5√x−2=y(y−4)√y−2−2x(√y−2−1)√2x+1=8x3−13(y−2)+82x−29 \right.$
Hệ phương trình